2002
DOI: 10.1128/mcb.22.4.1172-1183.2002
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin/Tcf Signaling Induces the Transcription of Axin2, a Negative Regulator of the Signaling Pathway

Abstract: Axin2/Conductin/Axil and its ortholog Axin are negative regulators of the Wnt signaling pathway, which promote the phosphorylation and degradation of ␤-catenin. While Axin is expressed ubiquitously, Axin2 mRNA was seen in a restricted pattern during mouse embryogenesis and organogenesis. Because many sites of Axin2 expression overlapped with those of several Wnt genes, we tested whether Axin2 was induced by Wnt signaling. Endogenous Axin2 mRNA and protein expression could be rapidly induced by activation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

87
1,328
5
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,547 publications
(1,425 citation statements)
references
References 51 publications
87
1,328
5
5
Order By: Relevance
“…Consistent with this idea, transcriptional analysis of FEnS/organoid cultures derived from control and Ret51 mice using a panel of epithelial differentiation markers revealed that, at a time point where most differentiation markers were only marginally reduced in cultures derived from Ret51 mice (Fig EV4D), there was a strong reduction in Axin2 transcript levels in these Ret51 cultures (Fig 6E). Axin2 is a commonly used readout of Wnt pathway activity: a signalling pathway that sustains intestinal stem cell proliferation and promotes both differentiation of Paneth cells in vivo and the maturation of FEnS to organoids ex vivo (Jho et al , 2002; van Es et al , 2005; Fordham et al , 2013; Clevers et al , 2014). To explore a possible positive feedback between Ret and Wnt signalling further, we treated immature cultures derived from wild‐type E16.5 small intestines, consisting exclusively of FEnS, with GDNF: a Ret ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this idea, transcriptional analysis of FEnS/organoid cultures derived from control and Ret51 mice using a panel of epithelial differentiation markers revealed that, at a time point where most differentiation markers were only marginally reduced in cultures derived from Ret51 mice (Fig EV4D), there was a strong reduction in Axin2 transcript levels in these Ret51 cultures (Fig 6E). Axin2 is a commonly used readout of Wnt pathway activity: a signalling pathway that sustains intestinal stem cell proliferation and promotes both differentiation of Paneth cells in vivo and the maturation of FEnS to organoids ex vivo (Jho et al , 2002; van Es et al , 2005; Fordham et al , 2013; Clevers et al , 2014). To explore a possible positive feedback between Ret and Wnt signalling further, we treated immature cultures derived from wild‐type E16.5 small intestines, consisting exclusively of FEnS, with GDNF: a Ret ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Whole-mount analysis of Wnt reporter Tg(TOPdGFP) transgenic embryos revealed that GFP expression is normally present around and within the lens (Dorsky et al, 2002;Nadauld et al, 2006;Paridaen et al, 2009), however, the cell types in which the Wnt/b-catenin pathway is active was not described. To determine where this pathway is activated at a cellular level, we performed in situ hybridization experiments with the known Wnt target genes axin2 and dkk1 and subsequently serially sectioned the embryos (Jho et al, 2002;Niehrs, 2006). axin2, a component of the protein complex that targets b-catenin for destruction, is expressed in the CMZ of wild-type embryos between 32 and 36 hours postfertilization (hpf; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt ligands have no effect on the accelerator, but act by relieving the brake. One of the target genes induced in response to Wnt is Axin2 which encodes a protein related to the Axin1 scaffold 10 . Axin1 is the least abundant molecule in the destruction complex and sets the limit on the numbers of such complexes in a cell 11 , although modulation of APC levels can also affect the capacity of the pathway 12 .…”
Section: Confusing Wnt Terminologymentioning
confidence: 99%